USE OF ACTIVE LEARNING METHODS IN HIGH SCHOOL - Moiseenko, R.M. (Pedagogy of Higher and Secondary Education, 2004)
The article reveals the necessity of personality-moving approaches to the development of a featured specialist at a higher educational establishment.